Combining L-Arginine with vitamin C improves long-COVID symptoms: The LINCOLN Survey - Raffaele Izzo; Valentina Trimarco; Pasquale Mone; Teresita Aloè; Massimo Capra Marzani; Antonio Diana; Giovanni Fazio; Mario Mallardo; Mauro Maniscalco; Giuseppe Marazzi; Nunzia Messina; Simone Mininni; et al. (Elsevier, 2022)
Introduction: Recent evidence suggests that oxidative stress and endothelial dysfunction play critical roles in the pathophysiology of COVID-19 and Long-COVID. We hypothesized that a supplementation combining L-Arginine (to improve endothelial function) and Vitamin C (to reduce oxidation) could have favorable effects on Long-COVID symptoms. Methods: We designed a survey (LINCOLN: L-Arginine and Vitamin C improves Long-COVID), assessing several symptoms that have been associated with Long-COVID to be administered nationwide to COVID-19 survivors; the survey also included effort perception, measured using the Borg scale. Patients receiving the survey were divided in two groups, with a 2:1 ratio: the first group included patients that received L-Arginine + Vitamin C, whereas the second group received a multivitamin combination (alternative treatment). Results: 1390 patients successfully completed the survey. Following a 30-day treatment in both groups, the survey revealed that patients in the L-Arginine + Vitamin C treatment arm had significantly lower scores compared to patients who had received the multivitamin combination. There were no other significant differences between the two groups. When examining effort perception, we observed a significantly lower value (p < 0.0001) in patients receiving L-Arginine + Vitamin C compared to the alternative-treatment arm. Conclusions: Our survey indicates that the supplementation with L-Arginine + Vitamin C has beneficial effects in Long-COVID, in terms of attenuating its typical symptoms and improving effort perception.